The Impact of Using FinTech Products in Enhancing Sustainable Competitive Advantage/An Analytical Study in Iraqi Banks Operating in the Kurdistan Region/Iraq - ساوين قادر محمود; فريدون نزار كريم; باسمة فالح النعيمي (Iraqi Journal for Administrative Sciences, 2025)
This study aimed to demonstrate the importance of using financial technology products as a modern financial experience in the banking sector and its role in enhancing sustainable competitive advantage. The study relied on the descriptive analytical approach in studying the various aspects of financial technology and sustainable competitive advantage, and testing the research hypotheses by preparing a questionnaire consisting of (42) paragraphs, which was distributed to Iraqi banks operating in the Kurdistan Region/Iraq. The answers were analyzed according to the statistical program (SPSS-28), in addition to measuring the validity and reliability of the questionnaire by testing the degree of credibility with the Cronbach's alpha coefficient for the purpose of testing and measuring the degree of credibility (reliability) in the responses received from the questionnaire questions. The research concluded that there is an awareness among those concerned in these banks of the importance of using financial technology products, as it contributes significantly to achieving sustainable competitive advantage in its five dimensions. The research also reached a set of recommendations, the most prominent of which is developing banking awareness among different segments of society by urging them to digital transformation.